2000
DOI: 10.1110/ps.9.7.1274
|View full text |Cite
|
Sign up to set email alerts
|

Topography of a 2.0 Å structure of α1‐antitrypsin reveals targets for rational drug design to prevent conformational disease

Abstract: Members of the serpin family of serine proteinase inhibitors play important roles in the inflammatory, coagulation, fibrinolytic, and complement cascades. An inherent part of their function is the ability to undergo a structural rearrangement, the stressed~S! to relaxed~R! transition, in which an extra strand is inserted into the central A b-sheet. In order for this transition to take place, the A sheet has to be unusually flexible. Malfunctions in this flexibility can lead to aberrant protein linkage, serpin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
195
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(201 citation statements)
references
References 51 publications
6
195
0
Order By: Relevance
“…2) in which the RCL is completely exposed. For example, the main chain trace within this region of CBG is identical to those of uncleaved human AAT (32)(33)(34), thermopin (35), and some noninhibitory serpins such as ovalbumin (36) and maspin (37). Interestingly, the conformation of the RCL observed in CBG also resembles that of other ligand-bound serpins, such as the complex of antithrombin with a pentasaccharide ligand (21, 38) (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…2) in which the RCL is completely exposed. For example, the main chain trace within this region of CBG is identical to those of uncleaved human AAT (32)(33)(34), thermopin (35), and some noninhibitory serpins such as ovalbumin (36) and maspin (37). Interestingly, the conformation of the RCL observed in CBG also resembles that of other ligand-bound serpins, such as the complex of antithrombin with a pentasaccharide ligand (21, 38) (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The liver tissue specimens were fixed in formalin and embedded in paraffin. Serial sections were stained with either hematoxylin or 2 The reactive center loop that binds to neutrophil elastase is shown in red, and ␤-sheet A is illustrated in green. The position of the Z mutation (Glu342Lys) is shown (arrow).…”
Section: Methodsmentioning
confidence: 99%
“…1 The average concentration of ␣ 1 -antitrypsin in plasma in individuals with 2 normal M alleles (Pi M) is approximately 1.3 mg/mL, with a half-life of 3 to 5 days. Biochemical and crystallographic studies have revealed that the structure of ␣ 1 -antitrypsin is based on three ␤-sheets (A-C) and an exposed mobile reactive loop that presents the P1-P1Ј methionine-serine residues as a pseudosubstrate for the target proteinase 2 (Fig. 1).…”
mentioning
confidence: 99%
“…Serpins are serine protease inhibitors, about 400 amino acid residues long (17-20), with an exposed reactive center loop near their carboxyl terminus (21,22). The P1 residue located in this loop determines the primary specificity of inhibition.…”
mentioning
confidence: 99%